(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article provides a geographic analysis of the ecological and cultural tourism potential in Uzbekistan. It explores tourist destinations, available resources, existing problems, and promising directions from a scientific perspective. The paper also offers practical recommendations for the sustainable development of these tourism sectors.